Factors associated with the management of Sexually transmitted infections (STIs) and sexual dysfunctions (SDs): A survey of Iranian-American physicians in California - Rashidian, Mitra; Minichiello, Victor; Knutsen, Synnove; Ghamsary, Mark (Advances in Social Sciences Research Journal, 2019)
Introduction. Knowledge on effective management strategy for sexual healthcare (i.e., sexual history taking, sexually transmitted infections, sexual dysfunctions) used by Iranian-American physicians remains a serious gap within current literature. Having this knowledge, and its impact on their patients, is essential, since discussions of sexually related topics are taboo in Iranian societies. Aim. We examined the Iranian-American physicians’ sexual healthcare management offered to their patients, within the context of the barriers, and the attitudes, inhibiting the discussion and provision of sexual healthcare. Methods. A self- administrated questionnaire was designed. 1,550 survey instruments were sent to Iranian-American physicians practicing in California. Factor analysis performed to detect relationships between correlated variables within the data. Results. 348 questionnaires (23% response rate) were returned. Four factors related to the effectiveness of sexual health care management were identified, which were internally consistent (a range of Cronbach’s alpha=0.89 to 0.94). Factors: (1) female sexual dysfunction, (2) history of sexual intercourse, (3) STI, and knowledge of disease, (4) male sexual dysfunction. Significant associations were found between variables: clinical specialty, religious affiliation, age, gender, and place of graduation. Conclusion. Results show all four factors may significantly impact the effectiveness of sexual health care management by Iranian-American physicians which can potentially influence quality of sexual healthcare for patients. Additional studies from this population and other subpopulations of US physicians are needed to design new strategies that reflect on physicians’ management on sexual healthcare delivery. If confirmed in other studies, our findings could have implications for training of medical graduates globally.